Rural Livelihood Diversification Strategies and Household Welfare in Bhutan. Issue 4 (September 2018) - Rahut, Dil; Mottaleb, Khondoker; Ali, Akhter
Abstract This paper analyzes rural livelihood diversification strategies and their impact on household welfare using the Bhutan Living Standard Survey 2012. The multinomial estimation shows that education, asset endowment, labor availability, and sex (male/female) of the household head play a vital role in livelihood diversification into non-agricultural sectors. Propensity score matching estimates illustrate that rural households diversifying outside agriculture have higher income and lower poverty levels compared to households pursuing only farming for their livelihoods. Livelihood diversification into non-farm activities can help reduce poverty levels in the range of 6–9 per cent, suggesting the importance of livelihood diversification in reducing poverty and increasing household income in Bhutan. Cet article analyse les stratégies de diversification des moyens de subsistance en milieu rural et leur impact sur le bien-être des ménages à l'aide du sondage de 2012 sur le niveau de vie au Bhoutan. L'estimation multinomiale montre que l'éducation, la dotation en capital, la disponibilité de la main-d'œuvre et le sexe (masculin/féminin) du chef de ménage jouent un rôle essentiel dans la diversification des moyens de subsistance dans les secteurs non agricoles. Les estimations du score de propension illustrent le fait que les ménages en milieu rural qui se diversifient en dehors de l'agriculture ont des revenus plus élevés et des niveaux de pauvreté inférieurs à ceux des ménages qui n'ont que l'agriculture pour leur subsistance. La diversification des moyens de subsistance vers des activités non agricoles peut aider à réduire les niveaux de pauvreté de l'ordre de 6 à 9%, ce qui montre l'importance de la diversification des moyens de subsistance pour réduire la pauvreté et augmenter le revenu des ménages au Bhoutan.